Curious minds : a Knight and Moon novel - Evanovich, Janet; Sutton, Phoef (Evanovich, Janet. Knight and Moon novel., 2016)
"Janet Evanovich, #1 New York Times bestselling author of the Stephanie Plum series, teams up with Emmy-winning writer Phoef Sutton for a brand-new series of thrillers featuring charmingly eccentric Emerson Knight and professional go-getter Riley Moon"--